Measurement of factors influencing online shopper buying decisions: A scale development and validation. (March 2021) - Fernandes, Semila; Venkatesh, V.G.; Panda, Rajesh; Shi, Yangyan
Abstract: The paper attempts to develop an 'Online Susceptibility Scale' (OSS) by focusing on the factors that influence shopper buying decisions in an online environment as they are not adequately addressed in the literature. The proposed scale supports the understanding of the impact of online information which leads to consumer decisions. The study involves qualitative and quantitative studies to develop the scale. Eleven items are identified for the scale development which were borrowed from literature and modified through focus group discussions. Exploratory Factor Analysis (EFA) resulted in three factor groups: Evidential online influence (five items), Confirmational online influence (three items), and Experiential online influence (three items). Confirmatory Factor Analysis (CFA) has validated the factor structure. Results indicate that the three factors explaining online information sources have a significant impact during buyer purchase decision-making. The study relates 'Online Susceptibility Scale' (OSS) to online retailers for exploring the online shopping influences, thereby managing their campaigns accordingly. Managerial and theoretical implications of this new scale are discussed. Highlights: The paper develops an online susceptibility scale. The study applies both qualitative and quantitative methodology to finalize the scale. An eleven-item scale helps to understand the factors that leads to consumer decisions. The scale has focus on Evidential online influence, Confirmational online influence, and Experimental online influence.